2020
DOI: 10.3389/fpubh.2020.00127
|View full text |Cite
|
Sign up to set email alerts
|

Group Nutrition Counseling or Individualized Prescription for Women With Obesity? A Clinical Trial

Abstract: Background: This study investigates the effects of group counseling vs. individual dietary prescription on physical, nutritional, and mental health in overweight or obese women. Methods: Seventy-four women aged 40-59 years with body mass index ≥ 25 kg/m 2 were randomized into 2 intervention arms: group nutrition counseling (GNC) or individualized nutrition prescription (INP). Twenty-seven women completed the 12-week intervention protocol. The GNC received counseling once a week and the INP received an individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…Four trials reported a reduction in ED risk within both intervention groups with no difference between groups 30,49,50,62 . Three trials reported no difference between intervention groups but did not report within group change 32,40,46 . No trials reported increased scores within or between groups.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Four trials reported a reduction in ED risk within both intervention groups with no difference between groups 30,49,50,62 . Three trials reported no difference between intervention groups but did not report within group change 32,40,46 . No trials reported increased scores within or between groups.…”
Section: Resultsmentioning
confidence: 94%
“…Most trials compared two or more weight management intervention groups, 28–69 and five compared a weight management to a weight–neutral intervention group using a non‐diet approach to health focusing on self‐acceptance and improving emotional well‐being 70–73 . Four trials included a no‐treatment or waitlist comparator group 14,71,73,74 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Current guidelines advocate regular, moderate PA to prevent infectious diseases (Campbell and Turner, 2018 ; Chastin et al, 2021 ). Individualized exercise prescription may reduce the cost of public health (Bolognese et al, 2020 ). While many factors can influence PA involvement, previous studies have begun to uncover the impact of gender, age, occupation, and other characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Current guidelines advocate regular, moderate PA to prevent infectious diseases (Campbell and Turner, 2018;Chastin et al, 2021). Individualized exercise prescription may reduce the cost of public health (Bolognese et al, 2020). While many factors can influence PA involvement, previous studies have begun to uncover the impact of gender, age, occupation, and other characteristics.…”
Section: Introductionmentioning
confidence: 99%